PREDICTION OF THE BODY WEIGHT OF ALGERIAN TAZEGZAWT SHEEP BREED FROM BODY MEASUREMENTS - Djaout, A.; El-bouyahiaoui, R.; Belkheir, B.; Moulla, F.; Mansouri, H.; Benidir, M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to determine the practicality of using linear body measurement traits to predict body weight of Tazegzawt sheep breed in the experimental station of INRAA in Bejaia. 38 female and 16 male aged over 2 years were used to investigate the relationships between live weight and body measurements such as scapular-ischial length, withers height, rump height, heart girth, chest depth, shoulder width, hip width, pelvis length and cannon perimeter. Pearson correlations showed a strong positive significant correlation (p<0.001) between BW and rump height (r=0.76), withers height (r=0.73) and the chest depth (r=0.73), with variations by sex. The results of multiple regression and stepwise showed that chest depth , the shoulder width and the cannon perimeter are the most valuable for estimating the body weight of the animals studied. A further implication of this study is to help smallholder farmers to estimate the live weight of their sheep from simple linear measurements and help the vet to determine suitable medication dosage during health care and required feed amount of the animal.